Effect of intermittent oven drying on lipid oxidation, fatty acids composition and antioxidant activities of walnut. (January 2016) - Fu, Maorun; Qu, Qingli; Yang, Xiaoying; Zhang, Xiaohui
Abstract: Compared with sun drying and direct oven drying methods, intermittent oven drying for walnut ( Juglans regia L .) drying was employed, and the consequent changes in lipid oxidation attributes, such as acid value (AV), peroxide value (POV), saponification value (SV), fatty acid composition, antioxidant activity (reducing power, superoxide anion scavenging activity, and DPPH free radical scavenging activity), lipoxygenase activity, and total phenols content (TPC) and total flavonoids content (TFC) were investigated in this study. Sun drying resulted in the highest AV, POV and SV, at the end of drying, that was 0.8 g/kg, 2.4 meq/kg, 230.9 g/kg, respectively, followed by direct oven drying and intermittent oven drying. Antioxidant activities and related compounds, TPC and TFC, were initially increased then declined during drying, and a significant correlation was found between antioxidant activity and TPC and TFC ( P < 0.05). The LOX activities of all samples showed an increasing trend, although those of the sun-dried samples were the lowest (0.43 μkat/mg). The walnuts dried with the intermittent oven drying method had much more linoleic acid than those dried by direct oven drying. Highlights: Lipoxygenase activity was correlated the lipid oxidation in the drying process. Phenolic and flavonoid were responsible for the antioxidant activity. Walnuts by intermittent oven drying had much more linoleic than others.